Implementasi Pembelajaran Gamelan Tradisional sebagai Media Stimulasi Perkembangan Kognitif Anak Usia Dini di KB Dewi Sartika Pacitan - Sri Hartutik; Diah Wahyuningsih (Lembaga Yasin AlSys, 2026)
Stimulation of early childhood cognitive development requires learning activities that are engaging, contextual, and aligned with children’s developmental characteristics. One medium that can be used is traditional gamelan learning as a form of local cultural integration in early childhood education. This study aimed to describe the implementation of traditional gamelan learning and its contribution to children’s cognitive development at KB Dewi Sartika Pacitan. This study used a descriptive qualitative approach with research subjects consisting of 6 children and 1 gamelan extracurricular teacher. Data were collected through observation, interviews, and documentation, and were then analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results showed that traditional gamelan learning had a positive impact on children’s cognitive development, particularly in the aspects of concentration, memory, the ability to follow instructions, recognition of musical instrument sounds, the ability to distinguish the shapes of musical instruments, and logical thinking through rhythm and turn-taking activities. The observation results showed that 33% of the children developed very well, 33% developed as expected, 17% were beginning to develop, and 17% had not yet developed optimally. The obstacles identified included limited musical instruments and differences in children’s ability to follow rhythm. Thus, traditional gamelan learning is effective as a medium for stimulating early childhood cognitive development as well as a means of preserving local culture in the context of early childhood education learning.